Effects of Work Life Balance on Staff Performance in the Telecommunication Sector in Kenya - Keino, Dinah C.; Kithae, Peter Paul (Archives of Business Research, 2016)
Work-life balance practices have positive impact on employee performance in an organisation in as much as work life imbalance has also been proved to have side effects of wellbeing of employees. This study looked at the effect of work life balance on staff performance in the telecommunication sector in Kenya. It used role theory and spill over theory to support the research. Descriptive research design was adopted in order to provide a framework to examine current conditions, trends and status of events regarding work life balance. The target population of the study was 390 senior staff working at Safaricom, Airtel, Telkom Kenya’s Orange and Essar Kenya’s Yu Headquarters in Nairobi. The study focused on the three levels of management who are directly dealing with the day to day management of the companies. Stratified random sampling technique was used since population of interest is not homogeneous and could be subdivided into groups or strata to obtain a representative sample. Structured questionnaires were used as method of data collection. Data analysis was done using both qualitative and quantitative methods. From the findings, it was evident that work life balance factors such as long working hours, overtime, lack of vacation, family responsibilities and family work conflict all negatively affects staff performance at work. The study recommended among others that companies in the telecommunication sector in Kenya need to review overtime working policy; introduce rotational work; adopt use of delegation and support employees through counseling and resources to meet family expectations and responsibilities. Finally, this study suggests that future studies explore other work life balance factors that could affect staff performance